PENGARUH VOLUME PERDAGANGAN DAN VARIAN RETURN TERHADAP BID-ASK SPREAD PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2012-2015 - Ardi Winarta, 12.05.52.0119; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2016)
This study is a study that examinedthe influence of trading volume activity and variant of return have an effect to bid-ask spread. Bid-ask spread is the difference between the lowest asked price and the highest price. In this study, the sampels used by 340 companies that listed on the Indonesian Stock Exchange in the year 2012 to 2015. Sampels choosed by purposive sampling method. In this study, the dependent variable is bid-ask spread and independen variable is stock price, trading volume activity and variant of return. To analyze the hypothesis used multiple regresion analysis. The results indicate thatTrading volume activity showed positive effect on bid-ask spread. Variant of return showed positive effect on bid-ask spread. Â Keywords: Bid-Ask Spread, Trading Volume Activity, Variant of Return